PENGARUH EKSPEKTASI GURU DAN SELF-EFFICACY SISWA TERHADAP HASIL BELAJAR PADA SISWA KELAS V DI SD GUGUS V CAKRANEGARA TAHUN PELAJARAN 2019/2020 - Karmita Zuriatin Asri; A. Hari Witono; L. Hamdian Affandi (Program Studi PGSD, FKIP, Universitas Mataram, 2020)
This research was aimed to know the influence of teachers’ expectation and student’s self-efficacy through the student’s learning achievement of the fifth grade elementary school students in Gugus V Cakranegara academic year 2019/2020. This research is correlational research with total population 259 students which separated in 6 schools.The technique of taken the sample used proportionate random sampling with total sample 157 students. The method of collecting the data that used in this research was documentation and questionnaire method. The achievement showed that the simple regression equation formula I was Y=29.674+0.742X1, so it was obtained the value of learning achievement was 29.674 (a=29.674) and the value of teacher’s expectation was (bX1=0.742). Therefore, thesimple regression equation formula II was Y=23.373+0.699X2, so it was obtained the value of learning achievement was 23.373 (a=23.373) and the value of student’S self-efficacy was 0.699 (bX2=0.699). Hence, in the hypothesis III, the dual regression equation formula was Y=25.937+0.319X1+0.401X2, so it was obtained the valueof learning achievement was 25.937 (a=25.937), the value of teacher’s expectationwas 0.319 and student’s self-efficacy was 0.401 (bX1=0.319; bX2=0.401). So it can be concluded that there were influence of teacher’s expectation and student’s self-efficacy through the students learning achievement in the fifth grade elementary school students in Gugus V Cakranegara academic year 2019/2020.